Multi‐GNSS Airborne Radio Occultation Observations as a Complement to Dropsondes in Atmospheric River Reconnaissance. Issue 21 (4th November 2021) - Haase, J. S.; Murphy, M. J.; Cao, B.; Ralph, F. M.; Zheng, M.; Delle Monache, L.
Abstract: Variations in the water vapor that atmospheric rivers (ARs) carry toward North America within Pacific storms strongly modulates the spatiotemporal distribution of west‐coast precipitation. The "AR Recon" program was established to improve forecasts of landfalling Pacific‐coast ARs and their associated precipitation. Dropsondes are deployed from weather reconnaissance aircraft and pressure sensors have been added to drifting ocean buoys to fill a major gap in standard weather observations, while research is being conducted on the potential for airborne Global Navigation Satellite System (GNSS) radio occultation (ARO) to also contribute to forecast improvement. ARO further expands the spatial coverage of the data collected during AR Recon flights. This study provides the first description of these data, which provide water vapor and temperature information typically as far as 300 km to the side of the aircraft. The first refractivity profiles from European Galileo satellites are provided and their accuracy is evaluated using the dropsondes. It is shown that spatial variations in the refractivity anomaly (difference from the climatological background) are modulated by AR features, including the low‐level jet and tropopause fold, illustrating the potential for RO measurements to represent key AR characteristics. It is demonstrated that assimilation of ARO refractivity profiles can influence the moisture used as initial conditions in a high‐resolution model. While the dropsonde measurements provide precise, in situ wind, temperature and water vapor vertical profiles beneath the aircraft, and the buoys provide surface pressure, ARO provides complementary thermodynamic information aloft in broad areas not otherwise sampled at no additional expendable cost. Plain Language Summary: Aircraft are deployed to make extraobservations and improve forecasts of the atmospheric rivers that carry moisture toward the coast of North America in northeast Pacific storms. Dropsondes are released from the aircraft to measure moisture, temperature and winds as they descend. We have increased the coverage of the aircraft measurements by making simultaneous measurements of the atmosphere using Global Positioning System (GPS) signals, and for the first time, signals from the European Galileo satellite system which provides 50% more radio occultation measurements. These airborne radio occultation (ARO) measurements of the refractive index of the atmosphere are based on travel time delays of the satellite signals, and are used to provide refractivity, moisture, and temperature profile information to the sides of the aircraft. The observations are assimilated into a mesoscale weather model to improve the initial moisture conditions used for the weather forecast. Cross sections through the updated model volume show variations in the refractivity that correspond to the atmospheric river features at low levels and cold front features at upper levels. Key Points: Flights over northeast Pacific atmospheric rivers provide dense airborne radio occultation and dropsonde data for assimilation in models The first Galileo RO profiles are compared with nearby Global Positioning System (GPS) profiles to assess accuracy in the troposphere The model refractivity anomaly distinguishes key characteristics of the atmospheric river including the low‐level jet and tropopause fold